High‐Resolution 3D Proton MRI of Hyperpolarized Gas Enabled by Parahydrogen and Rh/TiO2 Heterogeneous Catalyst. Issue 37 (24th June 2014) - Kovtunov, Kirill V.; Barskiy, Danila A.; Coffey, Aaron M.; Truong, Milton L.; Salnikov, Oleg G.; Khudorozhkov, Alexander K.; Inozemtseva, Elizaveta A.; Prosvirin, Igor P.; Bukhtiyarov, Valery I.; Waddell, Kevin W.; Chekmenev, Eduard Y.; Koptyug, Igor V.
Abstract Several supported metal catalysts were synthesized, characterized, and tested in heterogeneous hydrogenation of propene with parahydrogen to maximize nuclear spin hyperpolarization of propane gas using parahydrogen induced polarization (PHIP). The Rh/TiO2 catalyst with a metal particle size of 1.6 nm was found to be the most active and effective in the pairwise hydrogen addition and robust, demonstrating reproducible results with multiple hydrogenation experiments and stability for ≥1.5 years. 3D 1H magnetic resonance imaging (MRI) of 1 % hyperpolarized flowing gas with microscale spatial resolution (625×625×625 μm3) and large imaging matrix (128×128×32) was demonstrated by using a preclinical 4.7 T scanner and 17.4 s imaging scan time.